Does Malaria Cause Diarrhoea? A Systematic Review - Sey, Isatou C. M.; Ehimiyein, Ajoke M.; Bottomley, Christian; Riley, Eleanor M.; Mooney, Jason P. (Frontiers in Medicine, 2020)
Malaria is a systemic febrile disease that may progress to prostration, respiratory distress, encephalopathy, anaemia and death. Malaria is also an established risk factor for invasive bacterial disease caused, in the majority of cases, by invasive enteropathogens and in particular by non-Typhoidal Salmonella (NTS). Whilst various malaria-related pathologies have been implicated in the risk of NTS bacteraemia in animal models, including intestinal dysbiosis and loss of gut homeostasis, clinical evidence is lacking. As a first step in gathering such evidence, we conducted a systematic review of clinical and epidemiological studies reporting the prevalence of diarrhoea among malaria cases and vice versa. Database searches for ‘plasmodium’ and ‘diarrhoea’ identified 1771 articles; a search for ‘plasmodium’ and ‘gastroenteritis’ identified a further 215 articles. After review, 66 articles specified an association between the search terms and referred primarily, but not exclusively, to Plasmodium falciparum infections. Overall, between 1.6% and 44% of patients with acute malaria infection reported symptoms of diarrhoea (812 of 7267 individuals, 11%) whereas 5% to 42% of patients presenting to hospital with diarrhoea had an underlying malaria parasite infection (totaling 749 of 2937 individuals, 26%). However, given the broad range of estimates, a paucity of purposeful case control or longitudinal studies, and varied or poorly specified definitions of diarrhoea, the literature provides limited evidence to draw any firm conclusions. The relationship between malaria and gastrointestinal disturbance thus remains unclear. Carefully designed case-control studies and prospective longitudinal studies are required to confidently assess the prevalence and significance of intestinal manifestations of malaria parasite infection.